2015
DOI: 10.12659/aot.892596
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Comprehension of Key Concepts in Kidney Transplantation

Abstract: Educational level and older age are independent risk factors for poor comprehension. Kidney candidate knowledge of organs with increased risks is suboptimal despite previous consent to receive such organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…In the field of kidney transplantation, it is important to understand and be aware of the "seriousness" of the disease that caused the specific organ failure. However, it is necessary to realistically discuss what the transplantation means, to adequately inform the patient about transplant procedures and to support the willingness to face the surgery (10). Failure to adhere to immunosuppressive therapy may increase the risk of rejection of the transplanted organ and cause the loss of the latter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the field of kidney transplantation, it is important to understand and be aware of the "seriousness" of the disease that caused the specific organ failure. However, it is necessary to realistically discuss what the transplantation means, to adequately inform the patient about transplant procedures and to support the willingness to face the surgery (10). Failure to adhere to immunosuppressive therapy may increase the risk of rejection of the transplanted organ and cause the loss of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Age, gender and hemoglobin level interfered with "general health" in all patients. 10 Most of the kidney recipients were compliant with the immunosuppressants. The women were less compliant than men with medications (P = .02), and poor compliance with medications was more frequent among those with living unrelated donors (P = .04).…”
Section: (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…Available studies suggest longer duration of kidney disease is significantly associated with knowledge, whereas longer time on dialysis and complications negatively impact scores. 14 A more recent study undertaken by Ahsanuddin and colleagues 15 indicated that educational level and older age are independent risk factors for poor comprehension. However, both of these studies were conducted using tools that had not undergone formal psychometric testing.…”
mentioning
confidence: 99%